Controlled ionic conductivity via tapered block polymer electrolytes1. Issue 17 (27th February 2015) - Kuan, Wei-Fan; Remy, Roddel; Mackay, Michael E.; Epps III, Thomas H.
<x xml:space="preserve">Abstract</x> Tapered block polymer electrolytes have been developed and exhibited enhanced room temperature conductivity relative to poly(styrene-b-ethylene oxide) (P(S-EO)) and non-tapered poly(s-b-oligo-oxyethylene methacrylate) (P(S-OEM)) counterparts.